2007
DOI: 10.1590/s1020-49892007000800006
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional y composición corporal de niños pobres residentes en barrios periféricos de La Plata, Argentina

Abstract: Objetivos. Evaluar el estado nutricional y la composición corporal, como indicadores de la calidad de vida, en niños pobres que concurren a comedores comunitarios de La Conclusiones. En las comunidades infantiles estudiadas coexisten la desnutrición y el sobrepeso. La elevada prevalencia de retraso en el crecimiento (talla baja para la edad) y desnutrición global (peso bajo para la edad) y la grave reducción de la masa muscular, aun en niños con sobrepeso u obesidad, parecen ser consecuencias de un proceso ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
16

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 15 publications
3
13
0
16
Order By: Relevance
“…According to Mercer et al (2005), height deficits in children are the result of at least two variables: the occurrence of unfavorable socio-environmental circumstances during the early stages of life along with other living experiences transmitted by parents and grandparents and, the progressive deterioration in the living conditions of families over time. These observations were also reported by Oyhenart et al (2007) in some suburbs of the Gran La Plata including El Paligüe.…”
Section: Discussionsupporting
confidence: 83%
“…According to Mercer et al (2005), height deficits in children are the result of at least two variables: the occurrence of unfavorable socio-environmental circumstances during the early stages of life along with other living experiences transmitted by parents and grandparents and, the progressive deterioration in the living conditions of families over time. These observations were also reported by Oyhenart et al (2007) in some suburbs of the Gran La Plata including El Paligüe.…”
Section: Discussionsupporting
confidence: 83%
“…This scenario is in agreement with that observed in the most recent surveys [10][11][12][21][22][23][24] and with nationwide studies [25][26][27][28][29][30][31] as well as with those undertaken in other Latin American countries [3][4][5][6][7] .…”
Section: Discussionsupporting
confidence: 92%
“…Álvarez et al 6 in a study conducted on children of from 6 to 60 months, of the city of Antioquia, Colombia, found percentages of overweight and deficit of weight for height of 3.8% and 2.0%, respectively. Oyhenart et al 7 recorded a prevalence of overweight for height four times greater than of deficit (12.5% to 3.0%, respectively) on analyzing the nutritional status of children of Regarding height deficit, De Onis 37 observed that, in 2005, one-third of all the children below five years of age (about 178 million children) in low and medium income countries presented low height. Studies do, however, indicate a tendency to a decline both in the prevalence of low stature 38 as in that of low weight 37 in children, though such declines still fall short of the 50% reduction in undernourishment established as one of the Development Goals of the Millennium (MDM-1) 39 Millennium Development Goals (MDGs) 39 7 reported high prevalences in various Latin American countries and defined this as a public health problem which endures to the present day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations